Impact and Challenges of Integrating Artificial Intelligence and Telemedicine into Clinical Ophthalmology. Issue 3 (May 2021) - Ramessur, Rishi; Raja, Laxmi; Kilduff, Caroline L. S.; Kang, Swan; Li, Ji-Peng Olivia; Thomas, Peter B. M.; Sim, Dawn A.
Abstract : Abstract: Aging populations and worsening burden of chronic, treatable disease is increasingly creating a global shortfall in ophthalmic care provision. Remote and automated systems carry the promise to expand the scale and potential of health care interventions, and reduce strain on health care services through safe, personalized, efficient, and cost-effective services. However, significant challenges remain. Forward planning in service design is paramount to safeguard patient safety, trust in digital services, data privacy, medico-legal implications, and digital exclusion. We explore the impact and challenges facing patients and clinicians in integrating AI and telemedicine into ophthalmic care—and how these may influence its direction. Abstract : Supplemental Digital Content is available in the text